1983
DOI: 10.1073/pnas.80.11.3260
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity of actinomycin D and Netropsin binding to pBR322 DNA analyzed by protection from DNase I.

Abstract: A direct approach to determining the sequence specificities of equilibrium binding drugs by using the DNase protection technique is described. The method utilizes singly endlabeled restriction fragments and partial digestion of the drug fragment complex with DNase I. Microdensitometry of autoradiograms produced after electrophoretic separation of digestion products allows determination of sequences that are affected by drug binding. The feasibility of the technique for locating small ligands bound to DNA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 21 publications
6
61
0
Order By: Relevance
“…Netropsin is a close relative of distamycin containing two methylpyrrolecarboxamide rings and a guanidinium group in place of the third methylpyrrole moiety of distamycin (Zimmer, 1975) which exhibits very similar specificities for AT-rich regions of double helical DNA to distamycin (Van Dyke et al, 1982;Lane et al, 1983). In order to check whether distamycin and netropsin inhibit the specific Antp HD-DNA binding equally well we performed the same competition experiments with netropsin.…”
Section: Resultsmentioning
confidence: 99%
“…Netropsin is a close relative of distamycin containing two methylpyrrolecarboxamide rings and a guanidinium group in place of the third methylpyrrole moiety of distamycin (Zimmer, 1975) which exhibits very similar specificities for AT-rich regions of double helical DNA to distamycin (Van Dyke et al, 1982;Lane et al, 1983). In order to check whether distamycin and netropsin inhibit the specific Antp HD-DNA binding equally well we performed the same competition experiments with netropsin.…”
Section: Resultsmentioning
confidence: 99%
“…While intercalators cause major structural distortions, ligands which interact with DNA by groove binding effect only minor changes such as widening of the minor groove of DNA and localized bending of the DNA helix (29). Despite the minimal conformational changes caused by these agents, both distamycin and netropsin have been shown to alter DNA-directed enzyme reactions such as DNase I cleavage (15,24) and RNA polymerase transcription (8,37) In terms of DNA binding, previous studies have determined that these compounds bind in the minor groove of B-DNA with an AT base pair preference and do not intercalate (14). It has been suggested that the size of the DNA-binding site by the minor groove-binding compound is important to their potencies as antimicrobial agents (42).…”
Section: Resultsmentioning
confidence: 99%
“…We are at a loss to provide any cogent explanation and respectfully note the seeming complexity of the recognition processes involved. For the time being it must suffice to reiterate the belief [7,13,20] that apparent site sizes, and effects on flanking nucleotides, not only reflect the extent of true specific binding sites but are also governed by steric disturbances to the DNA helix which influence its ability to accommodate nucleases 1191 and serve as a substrate for cutting.…”
Section: The Apparent Size Of Binding Sitesmentioning
confidence: 99%
“…It is generally reckoned that berenil should bind preferentially to A+T-rich DNA [l, 5, 111. In this paper, we present the first (to our knowledge) footprinting study on the binding of berenil to DNA. In addition, because some previous footprinting work using netropsin and distamycin indicated that the binding-site sizes are longer than just the A + T-rich zones [7,81 we have investigated the acceptability of G . C base pairs in the preferred binding sites for all these drugs, whether within or adjacent to the A + T-rich zones, as well as the extent of conformational changes resulting from ligand binding.…”
mentioning
confidence: 99%